The motion picture teller - Cotterill, Colin (Soho Crime, Soho Press, Inc., 2023)
"Thailand, 1996: Supot, a postman with the Royal Thai Postal Service, hates his job. The only bright light in his life is watching classic movies with his best friend, Ali, the owner of a video store. These cinephiles adore the charisma of the old Western stars, particularly the actresses, and bemoan the state of modern Thai cinema-until a mysterious cassette, entitled Bangkok 2010, arrives at Ali's store. Bangkok 2010 is a dystopian film set in a Thailand run by chauvinistic Security Council officers-and Supot and Ali, immediately obsessed, agree it's the most brilliant Thai movie they've ever seen. But nobody else has ever heard of the movie, the director, the actors, or any of the crew. Who would make a movie like this and not release it, and why? Feeling a powerful calling to solve the mystery of Bangkok 2010, Supot journeys deep into the Thai countryside and discovers a curse around the motion picture, one that keeps Bangkok 2010 from ever being viewed. But does that mean its story can never be told? Colin Cotterill, author of the award-winning Dr. Siri Paiboun series, presents a complex, captivating narrative, interposed with fascinating flashes of Bangkok 2010's gritty screenplay, as the two intertwined tales of a Thailand in deep conflict begin to meet in the middle"--